Skill content in Malaysia's manufacturing trade: Keesing Approach / Mohamed Sharif Bashir and Zakariah A. Rashid (Faculty of Business and Management ; UiTM Press, 2005)
This paper examines Malaysia's resource allocation in production and trade activities. It employs the Keesing Approach of the Heckscher-Ohlin (HO) Theory in analysing the country's skill content of exports and imports. This paper utilises annual data covering 31 manufacturing industries for 1978, 1987 and 1996. The analysis is based on the sectoral skill coefficients, which represents the employment proportions on skill classes in each industry to measure the direct skill requirements for producing trade flows. The results confirm that the general skills of Malaysia s workforce still remain at a low level. In addition, the level of employment of high-skilled labour (managerial, professional, technical and supervisory categories) grows rapidly while that of low-skilled labour (semi-skilled and unskilled worker categories) remains stagnant since the 1990s. However the growth rate of high-skilled labour is considered low as compared to its prerequisites. There is certainly a need to upgrade the country's skill position, especially in the area of high-skill category. As a result, Malaysia must therefore switch from its current position of low-skilled labour to labour of a higher skill level than its overseas counterparts if it wants to maintain its comparative advantage in its trade flows.